A NEW EARLY SEMIONOTIDAE (SEMIONOTIFORMES, ACTINOPTERYGII) FROM THE UPPER LADINIAN OF MONTE SAN GIORGIO AREA SOUTHERN SWITZERLAND AND NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
The early history of the Semionotiformes is still scarcely known as, apart from the Permian Acentrophorus, most of the Early and Middle Triassic taxa traditionally ascribed to this order are often poorly known and/or they actually belong to other groups. Sangiorgioichthys aldae gen. n. sp. n. is described from the Upper Ladinian Kalkschieferzone (Upper Meride Limestone) of the Monte San Giorgio area on specimens coming from both Italy and Switzerland. The new genus is ascribed to the family Semionotidae as it shows several of the characters usually considered as diagnostic of the family itself, even if no real synapomorphies have been so far proposed for it. As a Semionotidae, Sangiorgioichthys gen. n. has an almost complete circumorbital series, large ascending process of the premaxilla, rostral and nasals almost tube-like, short maxilla, several suborbital bones posterior and ventral to the infraorbitals, long antero-dorsal process of the suboperculum, sensory canal system very rich in pores, mid dorsal ridge scales with an incipient spine. Peculiar characters of the new genus are dermal skull bones completely covered by ganoine, a very large ventral infraorbital almost attaining the anterior edge of the preoperculum, two ‘ventral’ suborbitals, very elongate anterior supraorbital bone,  dentition made of a number of tiny pencil-like teeth, anterior and posterior lateral line scales differentiated.
Keywords: Actinopterygii; Early Semionotidae; Ladinian; Monte San Giorgio